2020
DOI: 10.5194/wes-2020-58
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constructing Fast and Representative Analytical Models of Wind Turbine Main-Bearings

Abstract: Abstract. This paper considers the modelling of wind turbine main bearings using analytical models. The validity of simplified analytical representations used in existing work is explored by comparing main bearing force reactions with those obtained from higher fidelity 3D finite element models. Results indicate that there is good agreement between the analytical and 3D models in the case of a non moment-reacting case (such as for a spherical roller bearing), but, the same does not hold in the moment reacting … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Main-bearing research to date has mainly focused on load modelling (Kock et al, 2019;Hart, 2020;Wang et al, 2020;Zheng et al, 2020a;Stirling et al, 2021), load characteristics (Cardaun et al, 2019;Hart et al, 2019;Hart, 2020;Guo et al, 2021) and implications for fatigue damage (Zheng et al, 2020b;Loriemi et al, 2021). Lubrication conditions within the main bearing are generally not considered.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Main-bearing research to date has mainly focused on load modelling (Kock et al, 2019;Hart, 2020;Wang et al, 2020;Zheng et al, 2020a;Stirling et al, 2021), load characteristics (Cardaun et al, 2019;Hart et al, 2019;Hart, 2020;Guo et al, 2021) and implications for fatigue damage (Zheng et al, 2020b;Loriemi et al, 2021). Lubrication conditions within the main bearing are generally not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Load inputs to the Hertzian model are then determined using a simplified drivetrain representation and a static load balance, between applied hub loading and main-bearing force response, at each time step (Hart et al, 2019;Hart, 2020). This approach is possible due to the statically determinate nature of three-point-mount drivetrains in which the main bearing provides a force reaction only (Stirling et al, 2021), as is the case here. In Stirling et al (2021) it was shown that this simplified drivetrain representation is able to accurately recreate the radial response at the main bearing seen in a higher-fidelity, but still relatively simple, 3D finite element model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation